Technology Disruptions as Enablers of Organizational and Social Innovation in Digitalized Environment - Heli Koski; Helinä Melkas; Martti Mäntylä; Roel Pieters; Rauli Svento; Tuomo Särkikoski; Heli Talja; Juha Hyyppä; Harri Kaartinen; Hannu Hyyppä; Leena Matikainen (The Research Institute of the Finnish Economy (ETLA), 2016)
This paper illustrates how disruptive technologies primarily shaking the functioning of service sector are spreading to the manufacturing industries, and vice versa, and further change the roles of consumers and users. Software and data that first transformed the provision of services now lead the transition of traditional manufacturing companies towards the production of smart, connected products and fundamentally transform their operation and management. Along with the datafication of manufacturing companies, certain advanced digital technologies such as robotics originally developed for manufacturing purposes find their applications in services. Co-evolution of technology and service innovation will be in the center of transformation of health services towards the adoption of new service and care models with assistive and socially intelligent robots. Our paper also addresses that technology disruptions in a digitalized environment enable and facilitate transformation of consumers from mere end-users to active market participants who may not only design or customize products for their own needs but also to become active market players on the supply side. Technology disruptions may also challenge existing institutions. For instance, convergence of robotics and surveying resulting in decentralized, distributed collection of geographic data by vehicles equipped with sensors may make national mapping agencies obsolete.
Keywords: 330; Technology disruptions; digitalization; IoT; robotics; point clouds; renewable energy